Student Information System for Doña Rosario High School (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
A student information system is used for the educational system to manage the student data. Student information systems provide capabilities for registering a student in courses, documenting grading, and managing student data needs by the school. In this study, the researchers found the solution to the necessary problem that cannot be handled by our clients, such as difficulty in tracking student information; they cannot easily find the record of the student because of many procedures before they find the security of the system. The system can easily use an unauthorized person if they do not have security and storing documents they misplaced, that is, the record of the student can be misplaced if they do not keep it properly. In this study, the researchers tackled how to solve the problem of having a manual process. The researchers obtained considerable information that they need to build a computer-based system that can solve the problem. A design was used by the registrars’ office and other admin inside the school premises. In the process of the student information system, the user must log in to access the dashboard of the system. Inside the dashboard of the system, the user will see buttons, each of which has its function such as registration form, grading form, list of student form, and account form. The student can attempt to log in to their student information system; if the user reaches that limit, the system will automatically close. If the username and password are incorrect, then the system will show “access denied;” if it is correct, then the system will activate the dashboard. The main form has buttons, each of which has its function such as the registration button (if you click it, then you will access the registration form). The registration form can accept all inputs and save the record. The list of student forms can display the record of the student, such as LRN, year level, section, and first name and last name of the student who was already saved in the database of the system; it also has a report button for printing report. In the account button, before you access the account form, there is a code that you must fill up; only the admin can manage the account in the system. the dashboard also has a delete button for deleting the record of students and an update button for updating student records. The proposed system aims to upgrade the system for R.O. because the information system focuses on the admin side, which is not the student side. The proposed system was extremely useful, safe, and user-friendly. It can also help the school and its administration.
Keywords: student